Fertilizer nitrogen and global warming – A review - PRASAD, RAJENDRA; SHIVAY, YASHBIR SINGH (The Indian Journal of Agricultural Sciences, 2019)
Global warming is a burning issue today and agriculture especially the fertilizer nitrogen contributes to it significantly. It is also true that fertilizer nitrogen has been and will continue to be the key plant nutrient for increased cereal production in the world. It is estimated that by 2050 about 225-250 Tg N (Teragram or million metric tonnes) may be applied to agricultural crops as against 116 Tg N applied in 2016. In 2010, an estimated 100 Tg N was surplus from agricultural fields and released as nitrate (NO3) to ground and surface inland and marine waters and as ammonia (NH3) and nitrous oxide (N2O) to the atmosphere; the latter contributing to global warming. The NO2 so emitted has 298 times Global Warming Potential (GWP) as compared to CO2 and contributes significantly to global warming. The only way to reduce N2O emission from N fertilizer is to increase NUE in agriculture. Average nitrogen use efficiency (NUE) in cereal production at resent in the world is 40%. This can be achieved by introducing enhanced efficiency of N fertilizers, better agronomic management of N and by developing of more efficient N using crop plants. Research strategies are necessary in all the three areas and also there is an urgent need for determining ecofriendly dose of N for each crop.